The Monte Carlo Simulation of Three Antimicrobials for Empiric Treatment of Adult Bloodstream Infections With Carbapenem-Resistant Enterobacterales in China - Zou, Dongna; Yao, Guangyue; Shen, Chengwu; Ji, Jinru; Ying, Chaoqun; Wang, Peipei; Liu, Zhiying; Wang, Jun; Jin, Yan; Xiao, Yonghong (Frontiers in Microbiology, 2021)
Introduction: The aim of this study was to predict and evaluate three antimicrobials for treatment of adult bloodstream infections with Carbapenem-resistant Enterobacterales (CRE) in China, so as to optimize the clinical dosing regimen further. Methods: Antimicrobial susceptibility data of blood isolates were obtained from the Blood Bacterial Resistant Investigation Collaborative Systems in China. Monte Carlo simulation was conducted to estimate the probability target attainment (PTA) and cumulative fraction of response (CFR) of tigecycline, polymyxin B and ceftazidime/avibactam against CRE. Results: For the results of PTAs, tigecycline following administration of 50 mg q12 h, 75 mg q12 h, 100mg q12 h achieved＞90% PTAs when minimum inhibitory concentration (MIC) was 0.25 μg/ml, 0.5 μg/ml and 0.5 μg/ml, respectively; polymyxin B following administration of all tested regimens achieved＞90% PTAs when MICwas 1 μg/ml with CRE; ceftazidime/avibactam following administration of 1.25g q8 h, 2.5g q8 h achieved＞90% PTAs when MIC was 4 μg/ml, 8 μg/ml with CRE, respectively. As for CFR values of three antimicrobials, ceftazidime/avibactam achieved the lowest CFR values. The highest CFR value of ceftazidime/avibactam was 77.42% . For tigecycline and ceftazidime/avibactam, with simulated regimens daily dosing increase, the CFR values were both increased, the highest CFR of tigecycline values was 91.88%. For polymyxin B, the most aggressive dosage of 1.5 mg/kg q12 h could provide the highest CFR values (82.69%) against CRE. Conclusion: This study suggested that measurement of MICs and individualized therapy should be considered together to achieve the optimal drug exposure. In particular,pharmacokinetic (PK) and pharmacodynamics (PD) modeling based on local antimicrobial resistance data can provide valuable guidance for clinicians for the administration of empirical antibiotic treatments for Bloodstream Infections (BSIs).